Oral delivery of the non-β-blocking R-carvedilol enantiomer for skin cancer chemoprevention in SKH-1 mice - Pabitra K. Sardar; Steven Yeung; Ruby Tow; Jacqueline Luga; Matthew Huang; Ayaz Shahid; Bradley T. Andresen; Ying Huang (AAPS Open)
Abstract Purpose Skin cancer remains the most prevalent cancer worldwide with its incidence continuously rising. Previous studies have demonstrated the efficacy of the β-blocker carvedilol and its non-β-blocking enantiomer R-carvedilol in mitigating UV-induced skin carcinogenesis through topical application. The current study investigated whether orally administered R-carvedilol could prevent the development of skin cancer in SKH-1 mice. Methods Efficacy of orally delivered R-carvedilol was examined in SKH-1 mice exposed to repeated UV radiations for 25 weeks. Pharmacokinetic studies were conduced in mice to evaluate the drug levels in plasma and skin tissues. Pharmacodynamic studies were used to evaluate the effects of oral R-carvedilol and racemic carvedilol on mouse blood pressure. Results The findings revealed a statistical difference in tumor incidence between the group receiving R-carvedilol (20 mg/kg) and the UV-only control group (p = 0.00860), while lower doses of R-carvedilol (1.5 mg/kg and 5 mg/kg) did not exhibit a significant impact on tumor incidence. While tumor multiplicity varied significantly between groups (p = 0.005325), tumor volume analysis showed no statistical difference. Pharmacokinetic studies indicated that R-carvedilol accumulated in a dose-dependent manner within plasma and skin tissues. Notably, at a dosage of 32 mg/kg, oral R-carvedilol did not influence blood pressure, in contrast to carvedilol, highlighting its potential for chemoprevention with minimal cardiovascular side effects. Conclusions These data support oral administration of R-carvedilol as a viable strategy for the chemoprevention of skin cancer, given its efficacy and minimal impact on the cardiovascular system. Further studies determining the optimal doses and timing of drug treatment are warranted.